Appropriate type of digital camera for craniofacial data acquisition system - Ahmad, Anuar; Setan, Halim; Majid, Zulkepli; Chong, Albert K. (2006)
At present, digital camera can be purchased at reasonable price and could provide excellent output for the user. Today, a digital camera of high resolution is available and there are different types of digital camera. The user should select apropriate digital camera to suite their needs. In close range photogrammetry, digital camera has been widely employed for various applications in diversified field and could delivered the required needs or output. One of the application is the used of digital camera in medical photogrammetry. Digital camera has been reported used to acquire the information or data of human face. The data on the human face is known as craniofacial. It was proved that the compact digital camera is capable of providing the data. The Single Lens Reflex (SLR) digital camera could also be used for the acquisition of data from human face. In this study, an initial test on the performance of compact and SLR digital camera is carried out. Both types of digital cameras were calibrated using a common test field. From this study, it was found that the results of the SLR digital are superior than the results of compact digital camera. This study shows that the SLR digital camera has the potential to be used as a sensor for the craniofacial data acquisition system.